Instantaneous Frequency Image - Prado, Vander Teixeira; Higuti, Ricardo Tokio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The instantaneous frequency (IF) image is proposed in this work. It is obtained by the differentiation of the instantaneous phase (IP) image, which in turn is calculated by replacing the amplitude information with the IP in the delay-and-sum beamforming. The IP image is a coherence factor that reduces artifacts and sidelobes influence, and it will be shown that the IF image will keep these same positive characteristics. In amplitude images the reflector representation level varies according to the experimental conditions, even using time-gain compensation. In IP images, the reflector is represented by a - π to π rad variation. An important feature of the IF image is that a reflector is represented by a constant level that is determined by the central frequency of the signal. Farther reflectors are represented with similar magnitudes as closer ones, being less influenced by distance than IP images and resulting in better contrast. Amplitude, IP, and IF images are obtained from point spread function simulations and a medical phantom in different experimental cases: vertical distances, contrast reflectors, axial and lateral separation, and a sparse array. The improper choice of dynamic range can result in low contrast or nondetection of a reflector. For the IF image, the dynamic range is determined by the central frequency of the signal and the zero-mean Gaussian distribution of the IF of noise. The IF image can be used to improve reflector detection, as additional information to assist the interpretation of pixels intensities in conventional amplitude images, or as a new coherence factor.
Keywords: Arrays; dynamic range; instantaneous frequency (IF); instantaneous phase (IP); ultrasonic image